Strategi Kepala Sekolah Dalam Meningkatkan Efektivitas Manajemen Kelas - Isnaini Sapitri Br Purba; Abdul Fattah Nasution (JURNAL MANAJEMEN PENDIDIKAN, 2026)
School Principal's Strategy in Improving the Effectiveness of Classroom Management This study aims to analyze the principal's strategy in improving the effectiveness of classroom management at Al-Hijrah 2 Deli Serdang Private High School, focusing on the principal's strategy, the implementation of academic coaching and supervision, and supporting and inhibiting factors in its implementation. This study uses a qualitative descriptive approach. Data were obtained through interviews with the principal, vice principal, and subject teachers, and strengthened through observation and documentation studies. The results show that the principal's strategy is implemented through school vision-based planning, strengthening Islamic culture, dividing the roles of teachers and homeroom teachers, developing teacher competencies, academic supervision, coaching, and continuous monitoring and evaluation. Academic coaching and supervision contribute to improving teacher discipline, regular learning, and strengthening teachers' ability to manage the classroom, although follow-up supervision still needs to be carried out more consistently. Supporting factors for the strategy include internal school cooperation, religious culture, monitoring instruments, learning facilities, and foundation support, while inhibiting factors include the characteristics of adolescent students, teacher readiness, limited time of the principal, family influence, and the digital environment. This study concludes that the effectiveness of classroom management needs to be built through structural, professional, cultural, and ecological approaches.